Infra-Low Frequency Neurofeedback: A Systematic Mixed Studies Review - Bazzana, Fabian; Finzi, Sarah; Di Fini, Giulia; Veglia, Fabio (Frontiers in Human Neuroscience, 2022)
Abstract Neurofeedback training is increasingly applied as a therapeutic tool in a variety of disorders, with growing scientific and clinical interest in the last two decades. As neurofeedback methodology and targeted brain activity may vary significantly, the need to investigate the efficacy of specific neurofeedback protocols is apparent. Here we explore the clinical effects of Neurofeedback based on slow brain activity, the so-called Infra-Low Frequency (ILF) training, a recently developed methodology that gives indications of effectiveness in regulating the central nervous system. Methods: Literature search was first conducted according to PRISMA principles, described and then assessed using the MMAT appraisal tool. 18 well documented study of ILF-Neurofeedback training in human subjects were picked up and analysed. Reports include group interventions as well as single case studies. Results: This review confirms the heterogeneity of the research methodologies applied and allows one to highlight strengths and weaknesses of the selected studies. Research data indicates good potential for ILF-Neurofeedback to influence brain activity and neurovegetative parameters. From the clinical profile, a salient common observation is a high level of individualization as a specific characteristic of ILF-Training: this feature seems to correlate with effectiveness of ILF-Neurofeedback, but also poses a challenge for researchers in terms of producing controlled and comparable findings. After summarizing the key observations from the review, we propose some recommendations for future research on ILF-Neurofeedback.